Antitumor activity of N-acetyl-D-glucosamine-substituted glycoconjugates and combined therapy with keyhole limpet hemocyanin in B16F10 mouse melanoma model - Hulíková, K; Grobárová, V; Křivohlavá, R; Fišerová, A (Folia microbiologica, 2010)
N-Acetyl-D-glucosamine-substituted glycoconjugates (GCJs) with the polyamidoamine (GN8P) or calix[4]arene (GN4C) scaffold represent ligands for NKR-P1 molecule and induce NK cell-mediated cytotoxicity in vitro. The in vivo effect of these GCJs on mouse melanoma model was determined when administered either alone or in combination with non-specific immunostimulator keyhole limpet hemocyanin (KLH). All types of treatment significantly reduced the tumor growth on day 23, while GN4C as well as KLH were effective continuously (from day 14). The GN4C also induced the longest mean survival time (46.3 ± 11.1 d), followed by KLH+GN4C (36.4 ± 12.1), KLH (35.6 ± 6.5), KLH+GN8P (35.6 ± 6.7), and GN8P (32.4 ± 7.0), compared to controls (29.8 ± 3.6). The B16F10 specific cytotoxicity of peripheral blood cells was significantly elevated by both KLH and GN8P, whereas not by GN4C. KLH increased the effect of the GN4C, but did not influence that of GN8P. GN4C was proved to exert anticancer activity in mouse melanoma model. The combination of KLH with GCJs did not generate synergism.
Keywords: Hemocyanins; nádorové buněčné linie; Skin Neoplasms; Melanoma; výsledek terapie; Drug Therapy, Combination; Disease Models, Animal; Glycoconjugates; myši inbrední C57BL; mužské pohlaví; Acetylglucosamine; Drug Synergism; Mice; Cell Line, Tumor; Antineoplastic Agents; glykokonjugáty; Animals; hemokyanin; modely nemocí na zvířatech; synergismus léků; kombinovaná farmakoterapie; protinádorové látky; zvířata; melanom; Humans; nádory kůže; myši; adjuvancia imunologická; Adjuvants, Immunologic; Treatment Outcome; Mice, Inbred C57BL; lidé; Male; acetylglukosamin